Development of Work Sheets for Students (LKPD) in Writing Explanation Text - Charlina Charlina; Elvrin Septyanti (Hasanuddin University, 2019)
This study aims to describe the results of product trials based on the development of needs analysis results and product validation results that have been assessed. The product developed was LKPD in writing explanatory texts for high school students. This research is part of research and development (R&D) research. The method used in this research is qualitative and quantitative. Products are tested on students on a small scale. The product was tested on a class XI student of SMA Dharma Loka Pekanbaru. Data collection techniques were carried out through the questionnaire and test stages. Questionnaires were given to students to describe the quality of teaching materials (LKPD) that had been made through filling out questionnaire instruments. The test is given to students in accordance with the instructions and questions in the LKPD so a score is obtained based on established assessment criteria. Data obtained, analyzed through SPSS. The results of the data analysis provide an overview of the aspects of content eligibility, aspects of language readability, presentation of material, and graphics which have very strong correlations for the preparation of LKPD. This is indicated by the level of correlation of the aspect of content eligibility 0.852 with a significance level of 0.000 <0.5; aspects of language readability 0.759 with a significance level of 0.000 <0.5; presentation of material 0.979 with a significance level of 0.000 <0.5; and graphics 0.702 with a significance level of 0,000 <0.5.